Intelligent Electrical Device Load Scheduling for Building Energy Management - Setianingsih, Casi; Murti, Muhammad Ary; Saputra, Randy Erfa; Ilham, Willy Mochamad; Nurhadi, Mohammad Iqbal (International Journal of Integrated Engineering, 2022)
Currently, electrical energy is one of the primary needs in everyday life. Almost every device used for daily life uses electric power. However, the lack of user awareness in using electronic devices can cause monthly electricity bills uncontrolled, especially in office areas. To increase efficiency in the use of electrical energy in offices, a web-based management system and control of daily electronic expenses are created that can determine the monthly electricity bill target. In this system, the priority of electronic devices can also be determined and passed into an optimization algorithm using a priority queue algorithm and genetic algorithm for system efficiency and keep the data in the database. The optimal fitness value is in the 60th generation, obtained from testing the optimal fitness value. From the results of the execution time test, which shows an average execution time of 0.18 seconds, as well as the rules test, which has a 100% accuracy rate for genetic algorithm, and execution time test, which shows the number under one second, while test rules have an accuracy rate of 100% for priority queue algorithm, this indicates that the system is running following the designed regulations.